2003
DOI: 10.1046/j.1365-277x.2003.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Trend to better nutrition on Australian hospital menus 1986–2001 and the impact of cook‐chill food service systems

Abstract: Objective To assess trends in the nutritional quality of hospital menus and examine differences between menus used in hospitals with cook-chill or cook-fresh food services.Design Standard patient menus were analysed against 28 criteria to assess nutritional standards and compared to results from similar studies in 1986 and 1993.Setting Menus were collected from 80 hospitals in New South Wales, Australia, including 36 using cook-chill food service systems.Statistical Analysis Chi-squared analysis was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…Table (3) the daily fat intake was found that all the studied patients (100%) consumed less than the recommended daily intake. These results are in agreement with those of Clelland and Williams (2003) where they indicated a lower amount of fatty foods in the lists provided to inpatients. Therefore, there was no statistical significant relationship between fat intake and the type of disease.…”
Section: Resultssupporting
confidence: 92%
“…Table (3) the daily fat intake was found that all the studied patients (100%) consumed less than the recommended daily intake. These results are in agreement with those of Clelland and Williams (2003) where they indicated a lower amount of fatty foods in the lists provided to inpatients. Therefore, there was no statistical significant relationship between fat intake and the type of disease.…”
Section: Resultssupporting
confidence: 92%
“…The New South Wales Health Department developed a nutrition strategy in 1995 to promote better nutrition for people in NSW [15], and in line with this strategy, a number of area health services, including Hunter, adopted food and nutrition policies [1]. These initiatives may have improved the nutritional quality of foods for patients [16,17], but it is evident from renewed efforts to introduce policy and the high prevalence of unhealthy ‘red’ foods found in this study that there is also a need to improve the nutritional quality of food available for sale to staff, visitors and outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Many hospital foodservice production systems exist, including cook-fresh, cook-freeze and cookchill. The principal foodservice models in Australia are cook-chill and cook-freeze systems where food is preprepared and then rethermalised at required times (Greathouse et al 1989;McLelland & Williams 2003;Nettles & Gregoire 2006) and the traditional cook-fresh model. Other foodservice models, such as 'Steamplicity' whereby meals are plated in a central production unit prior to distribution to hospitals, then microwaved at short notice prior to meal times, have been implemented with success in the UK (Edwards & Hartwell 2006).…”
Section: Introductionmentioning
confidence: 99%